Multiscale Modeling and Experimental Characterization for Enhancement in Electrical, Mechanical, and Thermal Performances of Lithium-Ion Battery - Sharma, Snigdha; Panwar, Amrish K.; Tripathi, M. M. (Frontiers in Energy Research, 2022)
Lithium-ion batteries are the thriving energy storage device in multiple fields, including Automobiles, Smart Energy Grids, Tele-communication, and many more. Due to its high complexity in the electrochemical-electrical-thermal system, there are certain non-linear spatiotemporal scales for measuring the performance of the lithium-ion battery. The fusion of experimental and modeling approaches was used in this study to enhance the performance of lithium-ion batteries. This paper helps to evaluate the properties of LiMn2O4 (LMO) cathode material for Li-ion batteries and also characterize the crystalline nature, morphological structure, ionic and electronic conductivity of the electrode material with an experimental approach. In addition, a new computational model was designed and formulated to support various other models for computational investigation. This simulation was designed to analyze the one-dimensional structure of coin-cell batteries and also to evaluate the electrochemical and thermal performances. All the computational performance has been validated with the help of experimental techniques and also provides multiple benchmarks for future integration of experimental and computational approaches.